PENJABARAN PROSEDUR TRANSFER/NATURALISASI: TRANSLITERASI DAN KATEGORI MAKNA - Berliana, Berliana; Nu'man, Muhammad (Jurnal Al-Hibru, 2025)
Translation is the process of translating the meaning of text from the source language to the target language through certain stages, procedures and theories. A translator needs to have understanding, skills and strategies to avoid mistakes. This research aims to explain in detail the two translation procedures, namely the transfer procedure and the naturalization procedure. The method used is literature study, with data sources from related journals, articles and books. The transfer procedure involves transferring the source language to the target language phonetically, phonologically, graphically, as well as transliteration, which moves the alphabet from one system to another. Meanwhile, the naturalization procedure maintains words or expressions from the source text by adapting the spelling and rules of the target language, which is also known as adaptation. In conclusion, translation can use transfer or naturalization procedures, depending on the need to maintain the meaning and structure of the source language.